Research of the Characteristics of the Attitude of Working Women to the Global Risks of Industry 4.0 - Mariia PLUTOVA; Olga KOROPETS (Communications of International Proceedings, 2021)
Revealing the peculiarities of the subjective attitude of working women to the global social and economic risks of Industry 4.0 is an urgent task to ensure a high quality of life and well-being of employees in the conditions of rapid transformation of the world of work. The article presents the results of a survey conducted on the territory of the Russian Federation in 2021. The research was comparative in nature, the authors revealed the nature of the influence of the global socio-economic risks of Industry 4.0 on various aspects of the quality of life and well-being of working women, and also identified differences in the attitude of workers of different sex to economic and social threats. The survey involved 800 respondents working in various spheres of work: 388 women and 412 men aged 18 to 69 years. The results of the research showed that women are less confident in their competitiveness in the labor market, they are more concerned about replacing people with machines in their workplaces, they are more afraid of losing their jobs or transferring to part-time work. Women are more concerned about possible socio-economic changes in the quality and standard of their lives. At the same time, women are more positive about their professional flexibility and strive for more preservation of favorable working conditions and prevention of health-threatening situations.
Keywords: Well-Being; Employment; Quality of Life; Working Women; Global Risks of Industry 4.0.